Genome-Wide Identification and Expression of the PIN Auxin Efflux Carrier Gene Family in Watermelon (Citrullus lanatus) - Huaiguo Shang; Na Zhang; Zhouli Xie; Siyu Deng; Licong Yi; Xing Huang (Agriculture, 2021)
As one of the world’s most popular fruits, watermelon (Citrus lanatus) is cultivated in more than 3 million hectares across the globe, with a yearly yield of more than 100 million tons. According to ‘97103’ genome version 1, a previous study has shown that the watermelon genome consists of 11 PIN genes. However, the higher quality ‘97103’ genome version 2 was recently assembled by using PacBio long reads with the benefit of fast development sequencing technology. Using this new assembly, we conducted a new genome-wide search for PIN genes in watermelon and compared it with cucumber and melon genomes. We identified nine, nine, and eight PINs in watermelon, cucumber, and melon, respectively. Phylogenetic analysis revealed a distinct evolutionary history of PIN proteins in watermelon, which is shown by the orphan PIN6 in watermelon. We further conducted an expression analysis of the watermelon PIN genes in silico and by qRT-PCR. ClaPIN6 might not play an essential role during shoot regeneration, which is closely related to species-specific evolution. However, the up-regulated expression patterns of ClaPIN1-1 and ClaPIN1-3 indicated their important roles during shoot regeneration. The result of this research will benefit future studies to understand the regulating mechanisms of auxin in watermelon shoot regeneration.